Microwave-assisted synthesis of organically functionalized hexa-molybdovanadates. (8th December 2017) - Karoui, H.; Ritchie, C.
Abstract : The microwave-assisted reaction of (TBA)4 [β-Mo8 O24 ] and (TBA)3 [H3 V10 O28 ] with pentaerythritol or tris(hydroxymethyl)aminomethane yields polyanions with the general formula (TBA)2 [V3 Mo3 O16 (O3 –R)] (R: C5 H8 OH –1 ; R: C4 H6 NH2 –3 ). Post-synthetic esterification of1 yields the acylated derivative2, with all compounds being characterized in the solid and solution state. Abstract : The microwave-assisted reaction of (TBA)4 [β-Mo8 O24 ] and (TBA)3 [H3 V10 O28 ] with pentaerythritol or tris(hydroxymethyl)aminomethane yields polyanions with the general formula (TBA)2 [V3 Mo3 O16 (O3 –R)] (R: C5 H8 OH –1 ; R: C4 H6 NH2 –3 ). Post-synthetic esterification of1 yields the acylated derivative2, with all compounds being characterized in the solid and solution state.